Diseño de una ruta turística para fortalecer el turismo en la parroquia rural Julio E. Moreno del cantón Guaranda. Año 2022 - Calo Chitalogro, Melania Aracely (2023)
This research highlights the importance of the development of tourism, based on the offer of attractions that are relevant in the parish and that should be taken advantage of and seen as an opportunity for an economic source that will contribute to the improvement of the quality of life of the population. The project aims to design a tourist route to contribute to the strengthening of tourism in the parish of Julio E. Moreno. According to the research, the qualitative approach was used because it was based on bibliographic sources of authors who contributed to the analysis and development of the topic and the quantitative approach through which it was possible to determine the profile of the tourist. Based on the results it was established that the parish within its context is in stable conditions and that, despite the lack of services, it has relevant tourist potential, for which the design of the route was established with the attractions, signage, and budget that will allow obtaining the facilities, services and suitable adaptations for the established demand that focuses on local visitors that awaken their interest in touring and visiting the site, which is beneficial for the development and strengthening of local tourism. Keywords: route, tourism, development, demand, signage.